Influence of soil-ecological conditions on vegetation zonation in a western Mongolian lake shore semi-desert ecotone - Strauss, Andrea; Schickhoff, Udo (ERDKUNDE, 2007)
The Great Lakes Basin of W Mongolia encompasses vast stretches of deserts, semi-deserts, steppes as well as lakes and surrounding unique wetlands. These wetlands must be considered important elements of landscape ecosystems in semiarid/arid environments. On the other hand, the knowledge of even basic ecosystem components like soils and vegetation is still very fragmentary. We present a landscape-ecological study of vegetation and soil zonation along a western Mongolian lake shore-semi-desert ecotone. Our objective was to analyse fine-scale patterns of environmental variables along a marked environmental gradient and to find out their specific controls on the zonation of wetland plant communities. We followed the transect approach in order to document and understand patterns and changes in transitional areas between aquatic and upland habitats. We classified plant communities according to the Braun-Blanquet approach and subjected the vegetation and soil data sets to DCA and CCA (Detrended and Canonical Correspondence Analysis) in order to detect the main correlations between plant species turnover and changing site conditions along the transect. Analysis of the more or less belt-like vegetation zonation at the southwestern shore of Khar Us Nuur showed that five plant communities replace each other at a distance of only 250 m. In transitional areas, wetland plant communities form a mosaic or patch structure with shifting species dominances rather than sharp boundaries. Community replacements correspond to changing soil-ecological conditions. Along the transect from lake shore to the semi-desert, soil moisture, nitrogen and organic matter contents decrease, whereas soil pH and bulk density values increase. Calcium carbonate contents and soil salinity do not show uniform trends. Plant communities of the lake shore-semi-desert ecotone are distributed along a complex soil moisture/soil texture gradient. Soil moisture is the most critical environmental variable for vegetation patterns. Differences in soil moisture and related parameters like organic matter content, bulk density, and soil pH explain maximum vegetation variation. Within areas of more or less homogeneous soil moisture conditions in the wetland part of the transect, vegetation differentiation must be mainly attributed to differences in bulk density, soil pH, CaCO3 contents, and organic matter contents. Single soil parameters may vary widely within one plant community along the transect. Plant communities are obviously associated with a certain constellation of varying edaphical factors and have to adapt to a wider range of environmental conditions. Since grazing pressure concentrates on river and lake floodplains with its favourable soil water budget and productivity, all of the wetland communities are more or less changed in their species composition. Most of the original vegetation, including forests and shrublands, had already been destroyed.